Season of Colds and Flu is in Full Swing: Treating Cough - Svetlana V. Ilyina (Педиатрическая фармакология, 2018)
Acute cough is a common symptom and a common reason for seeking medical care. Patients with acute cough often practice selfmedication using over-the-counter (OTC) drugs. However, the efficacy and safety of OTC drugs are generally not tested in clinical settings. Moreover, a large number of side effects have been registered in children in response to OTC drugs. The article deals with the issues of the rationality of drug treatment in non-severe cases of acute respiratory infection accompanied by cough.